2010
DOI: 10.1098/rsbl.2010.0777
|View full text |Cite
|
Sign up to set email alerts
|

Will krill fare well under Southern Ocean acidification?

Abstract: Antarctic krill embryos and larvae were experimentally exposed to 380 (control), 1000 and 2000 µatm p CO 2 in order to assess the possible impact of ocean acidification on early development of krill. No significant effects were detected on embryonic development or larval behaviour at 1000 µatm p CO 2 ; however, at 2000 µatm p CO 2 development was disrupted before gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 20 publications
2
72
0
1
Order By: Relevance
“…Our study shows that deformities occur in lobster larvae raised in pCO 2 levels higher than 727 µatm, independently of temperatures being 10 or 18 • C. Deformities due to OA has been documented on the embryonic in some marine invertebrate species, often resulting in low or even no hatching success (Parker et al, 2009;Kawaguchi et al, 2010;Byrne, 2011), but also in the larval stages in a few species (Kurihara, 2008;Byrne et al, 2011, and references therein). Whiteley (2011) not affect larval conditions.…”
Section: Discussionmentioning
confidence: 95%
“…Our study shows that deformities occur in lobster larvae raised in pCO 2 levels higher than 727 µatm, independently of temperatures being 10 or 18 • C. Deformities due to OA has been documented on the embryonic in some marine invertebrate species, often resulting in low or even no hatching success (Parker et al, 2009;Kawaguchi et al, 2010;Byrne, 2011), but also in the larval stages in a few species (Kurihara, 2008;Byrne et al, 2011, and references therein). Whiteley (2011) not affect larval conditions.…”
Section: Discussionmentioning
confidence: 95%
“…Survival of krill embryos may be negatively affected by increasing ocean acidity (Kawaguchi et al 2013;Kawaguchi et al 2011), whilst a significant correlation has also been reported between krill density and Antarctic ozone depletion in the Antarctic Peninsula region, suggesting direct and/or indirect UV impacts on krill density (Mangel et al 2010;Naganobu et al 1999). The combined impact of these compounding threats on krill biomass may be considerable.…”
Section: Linking Climate Change To Species Responsesmentioning
confidence: 99%
“…Research combining experimental results and ocean circulation modelling shows survival of krill embryos may be negatively affected by increasing ocean acidity (Kawaguchi et al 2013;Kawaguchi et al 2011), with almost total Adults particularly susceptible to DNA damage and mortality due to UVB (Jarman et al 1999;Newman et al 1999). Adult behavioural changes, avoiding approximately 3.1d (Buchholz 2003).…”
Section: Observed Impactmentioning
confidence: 99%
See 2 more Smart Citations